Identification of a high diversity of Cryptosporidium species, genotypes and subtypes in a Nigerian Pediatric Population - HOLLAND, CELIA (My University, 2010)
A longitudinal study was conducted to determine the epidemiology of Cryptosporidium in 1,636 children in Nigeria. Oocyst prevalence ranged from 15.6% to 19.6% over one year. Cryptosporidium hominis (34), C. parvum (25), C. parvum/C. hominis (4), C. meleagridis (5), Cryptosporidium rabbit genotype (5), Cryptosporidium cervine genotype (3), and C. canis (1) were identified by polymerase chain reaction–restriction fragment length polymorphism analysis. Glycoprotein 60 subgenotyping showed that 28 amplifiable C. hominis isolates consisted of 12 subtypes that belonged to 5 subtype families (Ia, Ib, Id, Ie, and 1 novel subtype family, Ih) and 23 amplifiable C. parvum isolates consisted of 6 subtypes that belonged to 4 subtype families (IIa, IIc, Iii, and IIm). Three C. meleagridis isolates sub-genotyped by sequence analysis of the small subunit ribosomal RNA gene fragment were type 1. This study is the first one to genetically characterize Cryptosporidium species and subtypes in Nigeria and highlights the presence of a high Cryptosporidium diversity in this pediatric population.
PUBLISHED
Keywords: Cryptosporidium; Cryptosporidium; Immunology, Inflammation & Infection